2014
DOI: 10.1002/lt.23966
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration after living donor transplantation: Adult‐to‐adult living donor liver transplantation cohort study

Abstract: Background & Aims Adult-to-adult living donors and recipients were studied to characterize patterns of liver growth and identify associated factors in a multicenter study. Methods 350 donors and 353 recipients in A2ALL (Adult to Adult Living Donor Liver Transplantation Cohort Study) transplanted between March 2003 and February 2010 were included. Potential predictors of 3-month liver volume included total and standard liver volumes (TLV, SLV), the model for end-stage liver disease (MELD) score (in recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 34 publications
3
63
0
1
Order By: Relevance
“…While portal overflow injures the liver directly through nutrient excess, 17,21,22 endothelial activation 21 , and sinusoidal shear stress 19,23,24 , arterial vasoconstriction introduces secondary ischemic damage 25,26 . Several lines of work indicate that these insults are attenuated by reduction of portal flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While portal overflow injures the liver directly through nutrient excess, 17,21,22 endothelial activation 21 , and sinusoidal shear stress 19,23,24 , arterial vasoconstriction introduces secondary ischemic damage 25,26 . Several lines of work indicate that these insults are attenuated by reduction of portal flow.…”
Section: Discussionmentioning
confidence: 99%
“…When we examined the effects of modulation on the incidence of graft dysfunction (using the A2ALL definition 19 ), we noted that the modulated livers had an increased incidence of graft dysfunction consistent with the high frequency of left lobes and small grafts in the modulated population. A predictive model for the development of graft dysfunction identified modulation, left lobe, bilirubin, and donor age as predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to findings in other studies (20,32,37) [14,18]), and also during the first month, (RLL/TLV ranged from 64% to 89% [25,30,33,49], and mean liver growth from 115% to 181% [14,25,27]). After the initial month, the rate of regeneration slowed down, RLL/TLV reaching 74-80% (33,38,40,53), 72-96% (17,23,29,31,37,46,(51)(52), and 80-97% (16,23,26,29,31,33,40,53) in the first 3 months, 6 months, and 1 year, respectively, after donor right hepatectomy. In our study, liver volume increased to more than 2Â estimated remnant liver volume at the end of 1 year, yet ad integrum liver regeneration did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is one of the first to objectively demonstrate this fact. Only three other studies used paired sample t-test (27,36,53) to analyze the ad integrum restoration of liver function tests. They also found that ad integrum recovery does not occur even up to 1-2 years after donor hepatectomy.…”
Section: Discussionmentioning
confidence: 99%